2021
DOI: 10.1055/s-0041-1735129
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Abortion Complications after the Implementation of a Surveillance Network (MUSA Network) in a University Hospital

Abstract: Objective To evaluate the factors associated with abortion complications following the implementation of the good-practice surveillance network Mujeres en Situación de Aborto (Women Undergoing Abortion, MUSA, in Spanish). Methods A cross-sectional study with women who underwent abortion due to any cause and in any age group at UNICAMP Women's Hospital (part of MUSA network), Campinas, Brazil, between July 2017 and Agust 2019. The dependent variable was the presence of any abortion-related complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…16,17 Besides, failure of contraceptive methods might reflect the contraceptive use pattern of our country, in which oral contraceptives and condom are predominant compared with long-acting reversible contraceptives, such as intrauterine devices. 13 Our study showed that each week of gestational age increased 12.6% the risk of complications, while another study showed an increase in the number of complications by up to 20% in each week. 18 Pregnancies with higher gestational ages mean higher uterine volume, bigger amount of retained products of conception, and possible chorioamnionitis.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…16,17 Besides, failure of contraceptive methods might reflect the contraceptive use pattern of our country, in which oral contraceptives and condom are predominant compared with long-acting reversible contraceptives, such as intrauterine devices. 13 Our study showed that each week of gestational age increased 12.6% the risk of complications, while another study showed an increase in the number of complications by up to 20% in each week. 18 Pregnancies with higher gestational ages mean higher uterine volume, bigger amount of retained products of conception, and possible chorioamnionitis.…”
Section: Discussionmentioning
confidence: 42%
“…During the PrP, it was observed that the mean maternal age was 30. 13 In the PrP, 60.93% of the patients were married or living in a stable relationship, while 51.65% in the PP were single (p ¼ 0.005). In the PrP, 91.96% of patients did not have comorbidities, compared with 96.74% in the PP (p ¼ 0.031).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The authors identified that the factors associated with the presence of complications were higher gestational age and abortions resulting from contraceptive failure. It is noteworthy that approximately 30% of women became pregnant despite contraceptive use 22. In the same publication, the authors reported an approximate 90% rate of need for a uterine evacuation procedure, with a high rate of use of curettage and a dual method for uterine evacuation (misoprostol and curettage).…”
Section: Actions For Improvement In the Local Contextmentioning
confidence: 98%
“…It is noteworthy that approximately 30% of women became pregnant despite contraceptive use. 22 In the same publication, the authors reported an approximate 90% rate of need for a uterine evacuation procedure, with a high rate of use of curettage and a dual method for uterine evacuation (misoprostol and curettage). Aiming to analyse the effects of participation in the CLAP MUSA-Network on the use of safer methods, this same sentinel centre performed trend analyses of the use of MVA and medical abortion among 474 women and reported an increased use of MVA; medical abortion, however, remained less used.…”
Section: Actions For Improvement In the Local Contextmentioning
confidence: 99%